Days of infamy : how a century of bigotry led to Japanese American internment - Goldstone, Lawrence, 1947- (Scholastic Focus, 2022)
Provides an account of systemic racism against Japanese Americans, beginning with the 1880s Gold Rush that led to the eventual forced internment of Japanese American citizens during World War II.